Original PaperThe critical study about the correlation of tumor necrosis factor alpha, C-reactive protein and seromucoid level in serum with parameters of disease activity in seropositive and seronegative rheumatoid arthritis patients - Olczyk-Kwiecień, Barbara; Wisłowska, Małgorzata; Stępień, Krystyna (Reumatologia/Rheumatology, 2006)
Rheumatoid arthritis (RA) is a complex disease with genetic predisposition, closely related to autoimmunity and inflammation. Tumour necrosis factor alpha (TNF) plays an important role in both inflammatory and joint destructive pathways in RA. The aim of the study was to assess a possible correlation between RA disease activity and the level of TNF, CRP and seromucoid in serum in seropositive and seronegative RA patients in comparison to knee osteoarthritis (OA) patients. Blood from 30 seropositive RA patients (Group l), 30 seronegative RA patients (Group II) and from 30 patients with OA (Group III) who constituted the control group was collected. Serum TNF-alpha level was determined using an inhibition enzyme-linked immunosorbent assay (ELISA). The average level of TNF in serum in group I was 4.85±2.65 pg/ml, in group II it was 1.4±0.56 pg/ml and in group III it was 0.85±0.36 pg/ml. TNF-alpha was below 10 pg/ml in 97% of seropositive RA patients and in 93% of both seronegative RA patients and OA patients. Two patients with the higest levels of TNF in serum belonged to group I. They were in stage IV of the disease according to Larsen-Dale. In both groups of RA patients we found significantly higher (p<0.05) levels of CRP (means ±SEM-CRP: G l – 21.3±4.0 ml/l, G II – 18.8±4.0 ml/l, G III – 4.1±1.4 ml/l) and seromucoid (G I – 135.8±6.6 mg/dl, G II – 127.8±7.8 mg/dl, G III – 77.28±6.3 mg/dl). A correlation was observed between CRP levels and duration of morning stiffness (r=0.40 for G II), DAS 28 (r=0.42 for G II), ESR (r=0.58 for G II), alpha-1 globulin (r=0.54 for G l) and gamma globulin (r= 0.89 for G III) as well as between seromucoid levels and duration of morning stiffness (r=0.42 for G II), DAS 28 (r=0.42 for G II), ESR (r=0.64 for G II). RA patients treated aggressively had low levels of TNF in serum in our study. Inflammation parameters such as CRP and seromucoid correlated with disease activity.